LETTER TO THE EDITOR REGARDING: EVOLVING BUSINESS MODELS IN ORTHOTICS BY SCHNEIDER, N. - Connor Pardy; Steve Scott; Jenna Barnert; Carla Reimer (Canadian Prosthetics & Orthotics Journal, 2022)
The purpose of this letter is to continue the dialogue regarding the paper "Evolving business models in Orthotics" in the Canadian Prosthetics & Orthotics Journal Volume 4, Issue2, No.3, 2021. In it we present the perspective of the current Alberta Association of Orthotists and Prosthetists (AAOP) and provide additional context and information on historical events. Finally, we provide additional clarity on how costing is approached in the Province of Alberta (Canada) and the purported inequity in compensation between the two disciplines.